A Food System Approach for Sustainable Food-Based Dietary Guidelines: An Exploratory Scenario Study on Dutch Animal Food Products - van Dooren, Corné; Man, Laila; Seves, Marije; Biesbroek, Sander (Frontiers in Nutrition, 2021)
This study explores interconnections between food consumption and production of animal by-products in different food system scenarios within the scope of Dutch Food-Based Dietary Guidelines (FBDG). For this scenario study, a Microsoft Excel model was created including 7 scenarios with different quantities of eggs, milk, cheese, beef cattle, broilers, and pigs as input. Number of animals, intake of energy, animal protein, saturated fatty acids (SFA), trans fatty acids (TFA), salt, and greenhouse gas emissions (GHGE) and land use (LU) were calculated and compared to current consumption and reference values. Based on the concept of eating the whole animal, every recommended lean, unprocessed portion beef comes along with 1 non-recommended portion of beef (for pork 2 portions, for broilers 0.5 portion). The reference values for SFA, TFA and salt were not exceeded if the intake of meat is limited to 410 g/week. The scenarios with recommended 450 ml semi-skimmed milk and 40 g/day low fat cheese results in 36 g/day of butter as by-product, exceeding 3 times its acceptable intake. The near-vegetarian scenario with recommended amounts of eggs, milk, and cheese, includes only 1 portion beef/calf per 6 days and 1 portion chicken per 9 weeks as by-products. This scenario more than halves the GHGE and LU. Finally, the scenario including the maximum recommended amounts of animal products is reachable with half the current size of Dutch livestock. This conceptual framework may be useful in the discussion on how future sustainable FBDG can incorporate a more food system-based approach.